2014
DOI: 10.1021/jp501758b
|View full text |Cite
|
Sign up to set email alerts
|

Photostrictive/Piezomagnetic Core–Shell Particles Based on Prussian Blue Analogues: Evidence for Confinement Effects?

Abstract: High-quality core–shell particles, which associate a photostrictive core (Rb0.5Co­[Fe­(CN)6]0.8·zH2O, RbCoFe) and a ferromagnetic shell (Rb0.2Ni­[Cr­(CN)6]0.7·z′H2O, RbNiCr), were successfully grown by a multistep protocol based on coprecipitation in water. High-resolution transmission electron microscopy shows that well-defined heterostructures are formed and that the core–shell interface is abrupt with the epitaxial relationship [001](001)RbCoFe//[001]­(001)RbNiCr, confirmed by simulations of the X-ray diffr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 42 publications
6
46
4
Order By: Relevance
“…Access to the elastic moduli of PBA nanoparticles, which are largely unknown in molecule-based materials (bulk and nano-object), is of paramount importance for developing applications based on the mechanical properties of molecular materials, such as microelectromechanical systems (MEMS) [36,37] or mechanically coupled nano-heterostructures. [22,24,38] It is important to stress also that in this work, we provide an accurate value of Poisson's ratio. The mechanical characterization of coordination networks is challenging, especially at the nanoscale, but it is necessary for the development of new applications and for understanding phase-change phenomena governed by electron-lattice coupling.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Access to the elastic moduli of PBA nanoparticles, which are largely unknown in molecule-based materials (bulk and nano-object), is of paramount importance for developing applications based on the mechanical properties of molecular materials, such as microelectromechanical systems (MEMS) [36,37] or mechanically coupled nano-heterostructures. [22,24,38] It is important to stress also that in this work, we provide an accurate value of Poisson's ratio. The mechanical characterization of coordination networks is challenging, especially at the nanoscale, but it is necessary for the development of new applications and for understanding phase-change phenomena governed by electron-lattice coupling.…”
Section: Resultsmentioning
confidence: 95%
“…When one of the components undergoes an electronic phase transition, this coupling can even allow the switching of the properties of the second component. [22,24] Theoretical analysis has highlighted that the pressure the core (shell) can apply to the shell (core) upon the phase transition can be estimated if Young's moduli and Poisson's ratios of both components are known. [25] Then, combining the theoretical prediction with synthetic control of the core and shell thicknesses, the applied pressure on the core and the shell can be controlled, opening the way to monitoring the synergy between magnetism, optical, and electronic phenomena in PBA heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…This latter is related in most cases to a charge transfer between the cyanide‐bridged metallic centers, denoted charge transfer induced spin transition (CTIST), which can occur due to thermal, pressure, or light stimuli . Recently, the groups of Mallah, Talham, and Maurin succeeded in synthesizing fairly monodisperse core–shell PBA@PBA nanoparticles with a CoFe core exhibiting CTIST and an epitaxial ferromagnetic shell consisting of either NiCr or CoCr analogs. Their experiments revealed in each case remarkable couplings between the properties of the constituents.…”
Section: Size Reduction Effectsmentioning
confidence: 99%
“…36 For the pulse reverse deposition strategy, PB heterointerfaces were obtained by stepping the electrode potential between two different potentials with a periodic pulse frequency. 12,[99][100][101] In recent years, the universality of classical crystallization has been questioned upon investigations of crystal growth processes for assembly of Prussian blue, and few examples have shown that crystal growth may not follow such a classical crystallization process. Interfacial assembly by seed mediated growth A classical crystallization process starts from stable nuclei followed by a simple enlargement of the nuclei by unit-cell replication.…”
Section: Interfacial Assembly By Direct Electrodepositionmentioning
confidence: 99%